2019
DOI: 10.1136/bmjgh-2018-001122
|View full text |Cite
|
Sign up to set email alerts
|

Displacement, deprivation and hard work among Syrian refugee children in Lebanon

Abstract: BackgroundThe protracted Syrian war resulted in the largest refugee crisis of our time. The most vulnerable are children who face separation from parents, interruption of schooling and child labour. This study explores the living and working conditions of Syrian children in Lebanon.MethodsIn this cross-sectional study, we randomly selected 153 informal tented settlements and conducted interviewer-administered surveys among Syrian refugee working children in the Bekaa Valley in Lebanon. Those aged 8–18 complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 11 publications
1
41
0
Order By: Relevance
“…Syrian refugee children are exposed to various traumatic events such as loss of a loved one, witnessing combat or life threat during war and flight ( Gormez et al, 2018 ). Other social risk factors during post-migration period such as child labor, family violence, and child marriage also negatively affect the psychosocial wellbeing of Syrian refugee children in Turkey ( El Arab & Sagbakken, 2019 ; Falb et al, 2019 ; Habib et al, 2019 ; Usta et al, 2019 ; Wringe et al, 2019 ). Associated with these risk factors, studies indicate higher estimates of PTSD, depression, and anxiety among Syrian refugee children compared to Turkish children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Syrian refugee children are exposed to various traumatic events such as loss of a loved one, witnessing combat or life threat during war and flight ( Gormez et al, 2018 ). Other social risk factors during post-migration period such as child labor, family violence, and child marriage also negatively affect the psychosocial wellbeing of Syrian refugee children in Turkey ( El Arab & Sagbakken, 2019 ; Falb et al, 2019 ; Habib et al, 2019 ; Usta et al, 2019 ; Wringe et al, 2019 ). Associated with these risk factors, studies indicate higher estimates of PTSD, depression, and anxiety among Syrian refugee children compared to Turkish children.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by UNHCR in 2015 found that the highest risk for Syrian refugee children was psychological concern (51 %) followed by children dropped out of school (25 %) and child labor (11 %) ( UNHCR, 2015. p. 19 ). It is also important to mention that the risks identified in this study, including child labour ( Habib et al, 2019 ), child marriages ( El Arab & Sagbakken, 2019 ; Wringe et al, 2019 ) and domestic violence ( Falb, Blackwell, Stennes, Hussein, & Annan, 2019 ; Usta, Masterson, & Farver, 2019 ) in addition to the aforementioned higher risks, are factors which are likely to influence psychological wellbeing negatively.…”
Section: Vulnerabilities Of Refugee Children In Terms Of Health and Wmentioning
confidence: 94%
“…The study is based on a detailed protocol that was used in designing the study (see S1 Text, Study Protocol). The detailed study methodology is also reported in recently published work [4,6,50,51]. The study was approved by the Institutional Review Board at the American University of Beirut (IRB-RH1.08).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of Syrian refugees in the Bekaa are living in informal tented settlements (ITSs), which are collections of makeshift tents that provide inadequate and unsafe shelter [ 4 ]. Many such settlements are located near or on agricultural fields, which is consistent with agricultural housing practices from before the Syrian Civil War, when workers from Syria would come to tend the fields of the Bekaa on a seasonal basis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lebanon is hosting 1.5 million Syrian refugees, 75% percent of whom are women and children . According to the UN High Commissioner for Refugees (UNHCR), Syrian refugees have less access to primary healthcare services than the Lebanese population.…”
Section: The Concept Of Dignity In Access To Care: the Case Of Lebanonmentioning
confidence: 99%